WHEN TOUCH TALKS ABOUT BEAUTY: MEANINGS DISMANTLED BEHIND YOUTUBE BEAUTY VLOGS - Riskia Setiarini (UPT Penerbitan Universitas Jember, 2020)
This paper describes my perspective as a linguist whose concern is systemic functional linguistics sees touch functioning as a resource for meaning making on beauty-themed video blogs. Researches on touch are a few, and some reveal touch in relation to marketing-related issues, and some (if not few) are scrutinized under language analysis. One inspiring article compelled me do a research on the same topic but in different context (i.e. beauty vlogs) is from that brilliant work written by Bezemer and Kress (2014). Their idea sheds light on how social semioticians see it as both a non-mode as well as a mode of communication. Touch as the latter fulfills the criteria of language proposed by Halliday, comprising (inter)textual, interpersonal and ideational functions. Jewitt and Mackey (2018) even explore touch further. This tactile mode is researched by the conflation of multimodality and sensory ethnography, as multimodality alone is criticized for its subjective interpretative stance. Touch, according to Goffman (1979), is observed as a label embodied to women more than men. One example of the implementation of touch associated with what women mostly do is beauty vlogs  beauty-themed video blogs posted in social media. Together with other modes, this prehensile potential may carry several at-issue meanings. Using theories proposed by Bezemer and Kress (2014), Kress and van Leeuwen’s social semiotic communication (2006), Halliday’s SFL, and Goffman (1979), this article reveals if not to show beyond doubt how touch contains meanings (inward and outward meaning making, terms as suggested by Bezemer and Kress) linked to beauty-related issue. The data chosen are 5 (five) Youtube beauty vlogs of which topic is how to take care of the skin naturally, comprising 3 videos from Indonesian vloggers and the rest are from those outside Indonesia. These are selected as they are among mostly watched videos within 2018. Several touch(es) together with other resources, including linguistic texts taken in the form of shots assumed to have a particular and distinctive meanings are picked. The approach applied is social semiotics multimodalities, lying on how touch is made use by its users for constructing meanings and the finding is what Bezemer and Kress proposed is clearly applicable. In this way, touch reveals beauty in some ways. First, there proved to be a transduction where modes are moved to another mode. In this, the back of the hand, onto which touch is performed, functions as the face where beauty is associated. Second, there found also what so-called the dual materiality that touch is both visible and tactile in that both for the toucher and the (vlogs) viewers, and the last one is touch is proved not to be as a mode criterion, in that it is not used to address the interpersonal function, as both the touchers do not touch the viewers, for touch is not utilized as a means of communication. Keywords: metafunctions, touch, modes.